Motivation for aggressive religious radicalization: goal regulation theory and a personality × threat × affordance hypothesis - McGregor, Ian; Hayes, Joseph; Prentice, Mike (Frontiers in Psychology, 2015)
A new set of hypotheses is presented regarding the cause of aggressive religious radicalization. It is grounded in classic and contemporary theory of human motivation and goal regulation, together with recent empirical advances in personality, social, and neurophysiological psychology. We specify personality traits, threats, and group affordances that combine to divert normal motivational processes toward aggressive religious radicalization. Conducive personality traits are oppositional, anxiety-prone, and identity-weak (i.e., morally bewildered). Conducive threats are those that arise from seemingly insurmountable external forces and frustrate effective goal regulation. Conducive affordances include opportunity for immediate and concrete engagement in active groups that are powered by conspiracy narratives, infused with cosmic significance, encouraging of moral violence, and sealed with religious unfalsifiability. We propose that aggressive religious radicalization is rewarding because it can spur approach motivated states that mask vulnerability for people whose dispositions and circumstances would otherwise leave them mired in anxious distress.